THE HYPERBOLIC MENELAUS THEOREM IN THE POINCAR E DISC MODEL OF HYPERBOLIC GEOMETRY - Smarandache, Florentin; Barbu, C˘at˘alin (Italian Journal of Pure and Applied Mathematics, 2013)
In this note, we present the hyperbolic Menelaus theorem in the Poincar´e disc of hyperbolic geometry.